Accessibility to Reproductive Technologies by Low-Income Beef Farmers in South Africa - Nengovhela, Nkhanedzeni Baldwin; Mugwabana, Thinawanga Joseph; Nephawe, Khathutshelo Agree; Nedambale, Tshimangadzo Lucky (Frontiers in Veterinary Science, 2021)
This study address historical legacy of South Africa that has dual economies resembling low and high income beef sectors. Low-income herds are farmed mainly under communal village or land reform farms. The study focused on providing assisted reproductive technologies (ARTs) to the low-income sector including finding challenges to its implementation and adoption. The study was conducted in Limpopo, Mpumalanga and KwaZulu-Natal provinces using mixed methods that looked at cows and sectors stakeholders. Data collected and evaluated on cows included breed type, frame size, body condition, age parity, and lactation status. Cows were exposed to ART through synchronisation, oestrus detection, fixed time artificial insemination and pregnancy diagnosis. Qualitative data was collected to study perception of key stakeholders on ART implementation and adoption. Chi-Square Test was computed to determine the association among cow factors. Qualitative data was collected, coded and managed into themes using Nvivo Version 11. Themes that emerged were interpreted using critical social and systems thinking. Conception rate was not independent of provinces (P < 0.05), cow body condition score (BCS) and body frame size. KwaZulu-Natal cows had the highest conception rate at 66% (P < 0.05) than Limpopo (44%) and Mpumalanga (60%) provinces. Cows with a BCS higher than 3.5 had higher conception rate (P < 0.05) than those with BCS of less than 2.5 and 3. Interestingly, large framed cow size had higher conception rate than medium and small framed (P < 0.05) cows. The study achieved a 100% calf survival rate. Calving rate was influenced by body BCS, province and district (P < 0.05). Calving rate of 58% in Mpumalanga and 54% in KwaZulu-Natal was higher than that recorded in Limpopo at 36% (P < 0.05). Interestingly, cows with BCS of less than 2.5 had a higher calving rate than those with a higher body condition score of 3 (P < 0.05). Perception study results revealed many factors that could affect the adoption and implementation of ART in the study areas. The high success rate and above average reproductive performance led to North West and KwaZulu-Natal provinces adopting ART as part of their low-income beef sector support.